PENGARUH SOSIAL MEDIA MARKETING TIKTOK DAN FOOD QUALITY TERHADAP TRUST PADA SOSIS KANZLER DI ITSKes ICMe JOMBANG - Wisnu Mahendri; Siti Amilia Husen (KOLONI, 2022)
The purpose of this research is to analyze social impression marketing media on tiktok and food quality for trust of kanzler sausage in ITSKes ICMe Jombang. The technique to analyze data is using the linear regression formula. Collection of the data in this research is by spreading the questionnaire online through google form to college students from ITSKes ICMe who are using a tik tok app. Hypothetical test using statistic SPSS 26. The results showed that : 1) Social media marketing had an effect but not significant to trust, and indicating that 2) Food quality is affected and significant to build consumer trust.  Keywords: Sosial Media Marketing, Food Quality, Trust